Pharmacokinetics and pharmacodynamics of the injectable formulation of methadone hydrochloride and methadone in lipid nanocarriers administered orally to horses - Crosignani, N. [UNESP]; Luna, S. P. [UNESP]; Dalla Costa, T.; Pimenta, E. L.; Detoni, C. B.; Guterres, S. S.; Puoli Filho, J. N. [UNESP]; Pantoja, J. C. [UNESP]; Pigatto, M. C. (Wiley, 2017)
We investigated the thermal, electrical and mechanical antinociceptive and physiological effects (heart rate, respiratory rate, arterial blood pressure, head height and abdominal auscultation score), and pharmacokinetics, of 0.5 mg/kg of the injectable formulation (ORAL) or nanoparticulated methadone (NANO) given orally, in six adult mares, using a crossover, blind and prospective design. Repeated-measure models were used to compare parametric data between and within treatments, followed by Tukey's test. Nonparametric data were analysed with Wilcoxon signed-rank, adjusted by Bonferroni tests. Blood samples were also collected up to 6 h after dosing for plasma drug quantification by LC-MS/MS. Methadone pharmacokinetic parameters were determined by noncompartmental and compartmental approaches. There were no differences in pharmacodynamic parameters. No statistical differences were observed in the pharmacokinetic parameters from noncompartmental analysis for both groups, except a significant decrease in peak plasma concentration, increase in apparent volume of distribution per fraction absorbed (Vdss/F) and increased mean residence time (MRT) for NANO. One-compartment open model with first order elimination best described the pharmacokinetic profiles for both groups. Neither ORAL nor NANO administered orally to horses produced antinociception. The nanoencapsulated formulation of methadone given orally to horses did not improve methadone pharmacokinetic parameters or increased systemic body exposure to methadone.